2016
DOI: 10.18632/oncotarget.12208
|View full text |Cite
|
Sign up to set email alerts
|

miR-135a promotes gastric cancer progression and resistance to oxaliplatin

Abstract: Resistance to oxaliplatin (OXA)-based chemotherapy regimens continues to be a major cause of gastric cancer (GC) recurrence and metastasis. We analyzed GC samples and matched non-tumorous control stomach tissues from 280 patients and found that miR-135a was overexpressed in GC samples relative to control tissues. Tumors with high miR-135a expression were more likely to have aggressive characteristics (high levels of carcino-embryonic antigen, vascular invasion, lymphatic metastasis, and poor differentiation) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…As shown in Table 3, limited studies have been conducted to investigate the roles of miRNAs in the resistance mechanisms to other chemotherapy drugs. MiR-155-5p, miR-34c-5p, and miR-21 were found to be related to PTX resistance; [65][66][67] miR-361-3p, miR-135a, and miR-27a affect OXA resistance; [68][69][70] miR-1284 and miR-647 regulated VCR resistance; 71,72 and miR-200a inhibited taxol resistance, while miR-361-5p suppressed docetaxel Notes: *Targets genes were confirmed by Western blotting, RT-qPCR or dual-luciferase. **Upregulation (↑) or downregulation (↓) of miRNAs enhance chemosensitivity.…”
Section: Other Single-drug Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Table 3, limited studies have been conducted to investigate the roles of miRNAs in the resistance mechanisms to other chemotherapy drugs. MiR-155-5p, miR-34c-5p, and miR-21 were found to be related to PTX resistance; [65][66][67] miR-361-3p, miR-135a, and miR-27a affect OXA resistance; [68][69][70] miR-1284 and miR-647 regulated VCR resistance; 71,72 and miR-200a inhibited taxol resistance, while miR-361-5p suppressed docetaxel Notes: *Targets genes were confirmed by Western blotting, RT-qPCR or dual-luciferase. **Upregulation (↑) or downregulation (↓) of miRNAs enhance chemosensitivity.…”
Section: Other Single-drug Resistancementioning
confidence: 97%
“…73,74 Among the above-mentioned miRNAs, only miR-135a, miR-1284, and miR-647 were studied both in vitro and in vivo. 69,71,72 Interestingly, miR-361-3p and miR-361-5p were reported to regulate the resistance of different drugs. 68,74 This indicates that to best exploit the potential of microRNA-based tumor therapies, we need to pay attention to both the 3p-and 5p-arms of the same miRNA in addition to considering the functions of different miRNAs.…”
Section: Other Single-drug Resistancementioning
confidence: 99%
“…185 Methylation of miR-137 steadily increases in normal gastric tissue, chronic gastritis, and GC tissue, 186 and treatment of GC cell lines with 5-aza-CdR and 4 phenylbutyric acid activates previously silenced miR-512-5p, causing its raised levels to induce cell apoptosis. 151 The miRNA CpG hypermethylation was currently determined in GC mucosae with H. pylori infection, displaying a (7.2-15.5)-fold higher than that in normal gastric mucosae. 184 Another GC-related miRNA-34c has a CpG island nearing the transcription begin site of pri-miR-34c.…”
Section: Epigenetic Alternations In Gastric Carcinomamentioning
confidence: 99%
“…Tsai et al showed that the expression of miRNA‐34b, miRNA‐127‐3p, miRNA‐129‐3p, and miRNA‐409 used to be frequently decreased in GC cell lines with CpG‐rich methylation . Methylation of miR‐137 steadily increases in normal gastric tissue, chronic gastritis, and GC tissue, and treatment of GC cell lines with 5‐aza‐CdR and 4 phenylbutyric acid activates previously silenced miR‐512‐5p, causing its raised levels to induce cell apoptosis . The miRNA CpG hypermethylation was currently determined in GC mucosae with H. pylori infection, displaying a (7.2–15.5)‐fold higher than that in normal gastric mucosae .…”
Section: Epigenetic Alternations In Gastric Carcinomamentioning
confidence: 99%
“…For oxaliplatin resistance, the oncogenic miR-27a has been found to enhance MDR properties by inducing MDR1/P-gp, lung resistance protein (LRP) and Bcl-2 expression in gastric cancer [97]. Similarly, miR-135a has also been shown to potentiate oxaliplatin resistance of gastric cancer cells by down-regulating expression of E2F transcription factor 1 (E2F1) and death-associated protein kinase 2 (DAPK2) [98].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%